microRNA Expression and Its Association With Disability and Brain Atrophy in Multiple Sclerosis Patients Treated With Glatiramer Acetate - Dominguez-Mozo, María I.; Casanova, Ignacio; De Torres, Laura; Aladro-Benito, Yolanda; Perez-Perez, Silvia; Garcia-Martínez, Angel; Gomez, Patricia; Abellan, Sara; De Antonio, Esther; Lopez-De-Silanes, Carlos; Alvarez-Lafuente, Roberto (Frontiers in Immunology, 2022)
Background: MicroRNAs are small non-coding RNA that regulate gene expression at a post-transcriptional level affecting several cellular processes including inflammation, neurodegeneration and remyelination. Different patterns of miRNAs expression have been demonstrated in multiple sclerosis compared to controls, as well as in different courses of the disease. For these reason they have been postulated as promising biomarkers candidates in multiple sclerosis. Objective: to correlate serum microRNAs profile expression with disability, cognitive functioning and brain volume in patients with remitting-relapsing multiple sclerosis. Methods: cross-sectional study in relapsing-remitting multiple sclerosis patients treated with glatiramer acetate. Disability was measured with Expanded Disability Status Scale (EDSS) and cognitive function was studied with Symbol Digit Modalities Test (SDMT). Brain volume was analyzed with automatic software NeuroQuant ®. Results: We found an association between miR.146a.5p (rs: 0.434, p=0.03) and miR.9.5p (rs: 0.516, p=0.028) with EDSS; and miR-146a.5p (rs: -0.476, p=0.016) and miR-126.3p (rs: -0.528, p=0.007) with SDMT. Regarding to the brain volume, miR.9.5p correlated with thalamus (rs: -0.545, p=0.036); miR.200c.3p with pallidum (rs: -0.68, p=0.002) and cerebellum (rs: -0.472, p=0.048); miR-138.5p with amygdala (rs: 0.73, p=0.016) and pallidum (rs: 0.64, p=0.048); and miR-223.3p with caudate (rs: 0.46, p=0.04). Conclusions: These data support the hypothesis of microRNA as potential biomarkers in this disease. More studies are needed to validate these results and to better understand the role of microRNAs in the pathogenesis, monitoring and therapeutic response of multiple sclerosis.